Demonstrations on Happy seeder in wheat to stop paddy residue burning - Chandel, Rupinder; Singh, Kuldeep; Boparai, Arpan (Indian Farming, 2019)
The total geographical area of Jalandhar district is 2.66 lakh ha, occupying 5.3% of the total geographical area of the state and situated between the fertile agricultural land of rivers Beas and Sutlej, covering 11 blocks and 954 villages which are fully electrified and well connected with all weather roads. Temperatures in the summer vary from average highs of around 48ºC to average lows of around 25ºC and winter temperatures have average highs of 19ºC to lows of -7ºC. The climate is dry on the whole, except during the brief southwest monsoon season during July and August. The average rainfall of the district is 700 mm. The agricultural productivity is very high, i.e. 41.09 and 48.47 q/ha for paddy and wheat, respectively, in the district which has been achieved with assured irrigation, use of HYV seeds, good infrastructural support, etc. The fertilizer consumption of the district is 225 kg/ha of cropped area.